Correlation of severity of dengue with serum aminotransferase levels - Javed, Syed; Singh, Prabhat; Paliwal, Sanjay Kumar (International Journal of Advances in Medicine, 2021)
Background: In dengue, association of fever (most common presenting symptom) with hepatic involvement can be relatively more serious. Such patients may have raised serum aminotransferase levels as well as can be more prone to bleeding due to deranged liver functions. Thus, the present study was conducted with an objective to correlate these enzyme levels with the severity of dengue fever. Methods: This prospective, observational study was carried out for 1.5 years at a tertiary care teaching hospital in southern Rajasthan after ethics committee approval. Those patients diagnosed with dengue, admitted at this tertiary centre, aged 18 years and above and willing to give consent for participation, were included in the study. Patients were assessed for clinical features of dengue along with both laboratory and radiological investigations. Severity of dengue was correlated with aminotransferase levels. Data analysis was carried out using appropriate statistical tests. Results: Total 200 patients were analysed. Mean age was 36.92±14 years while male: female ratio was 1.23:1 in the study population. All patients (100%) had fever whereas shock and bleeding tendency were noted in 16 (8%) and 4 (2%) patients respectively. Majority 130 (65%) patients had moderate dengue. Raised aminotransferase levels were noted in approximately 65% study patients out of which nearly 40% patients had moderate dengue. Correlation of raised aminotransferase levels with thrombocytopenia, shock, bleeding tendency were not statistically significant. Conclusions: Serum aminotransferase levels were elevated in moderate dengue patients. However, there was no significant correlation of raised enzyme levels with thrombocytopenia, presence of shock and bleeding tendency or as the severity of dengue increases. Thus, it is quite subjective whether to predict severity of dengue from raised enzyme levels or not.